Dualitas Kepemimpinan: Eksistensi Masyarakat Adat (Pakraman) Desa Kutuh Bali Menuju Desa Anti Korupsi dan Terkaya se-Indonesia - Amalia Syauket; Bambang Karsono (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Usually in a village there is only one leader. However, this does not apply in Bali, namely the Kutuh Traditional Village. Kutuh Village is led by 2 people with different functions and jobs. Between the two by calling, its leadership duality, not dualism. Leadership that is mutually beneficial and supports each other, strives together to build Kutuh village towards an advanced village. This empirical research has been ongoing since 2021 and has interviewed village officials, the indigenous people of Kutuh-Bali Village aim to find out how the synergy between the Head of the Service Village and the Head of the Traditional Village of Kutuh Village in making their village advanced by optimizing the Village Fund and even getting the title as an anti-corruption village. corruption and the richest village in Indonesia. This study draws the conclusion that the duality of leadership is harmoniously intertwined between the village head of the